Trait Anxiety Mediates Impulsivity and Suicidal Ideation in Depression During COVID-19 Pandemic - Cheng, Xinyu; Zhang, Yi; Zhao, Di; Yuan, Ti-Fei; Qiu, Jianyin (Frontiers in Psychiatry, 2022)
Suicidality in patients with major depressive disorder (MDD) has been an urgent affair during the COVID-19 pandemic. It is well-established that impulsivity and trait anxiety are two risk factors for suicidal ideation. However, literature is still insufficient on the relationships among impulsivity, (state/trait) anxiety and suicidal ideation in individuals with MDD. The present study aims to explore the relationships of these three variables in MDD patients during the COVID-19 pandemic through three scales, including Barrett Impulsivity Scale (BIS), State-Trait Anxiety Scale (STAI) and Self-rating Idea of Suicide Scale (SIOSS). Sixty-three MDD patients (low SIOSS group and high SIOSS group, which were split by the mean score of SIOSS) and twenty-seven well-matched healthy controls were analyzed. Our results showed that the high SIOSS group had higher trait anxiety (p < 0.001, 95% CI = [−19.29, −5.02]) but there was no difference in state anxiety (p = 0.171, 95% CI = [−10.60, 1.25]), compared with the low SIOSS group. And the correlation between impulsivity and suicidal ideation was significant in MDD patients (r = 0.389, p = 0.002), yet it was not significant in healthy controls (r = 0.285, p = 0.167). Further, mediation analysis showed that trait anxiety significantly mediate impulsivity and suicidal ideation in patients with depression (total effect: β = 0.304, p = 0.002, 95% CI = [0.120, 0.489]; direct effect: β = 0.154, p = 0.076, 95% CI = [−0.169, 0.325]), indicating impulsivity influenced suicidal ideation through trait anxiety in MDD patients. In conclusion, our results suggested that trait anxiety might mediate the association of impulsivity and suicidal ideation in MDD patients. Clinicians may use symptoms of trait anxiety and impulsivity for screening when actively evaluating suicidal ideation in MDD patients, especially in the setting of COVID-19 pandemic.